Cytotoxicity Evaluation of Different Types of CAD/CAM Blocks - Fikret Özgür Coşkun; Semanur Özüdoğru; Mustafa Hayati Atala; Giray Buğra Akbaba (Selcuk Dental Journal)
Aim: The aim of this study is to determine the cytotoxic effects of Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM) blocks produced by different companies on human peripheral blood lymphocytes by MTT assay. Methods: Six different CAD/CAM materials were investigated: feldspar ceramic VM (Vitablocks Mark II ), resin nano-ceramic LU (Lava Ultimate), hybrid ceramic C (Cerasmart), leucite-reinforced ceramic LRF (GC LRF), zirconia-reinforced lithium silicate ceramic VS (Vita Suprinity), polymer-infiltrated ceramic-network VE (Vita Enamic). A total of 36 disc-shaped samples (Ø: 5 mm; h: 2 mm) were prepared from commercial blanks and blocks. Cell proliferation and cytotoxicity were assessed at 24h and 48h using MTT assay. The data were statistically evaluated with the Two-way ANOVA test (p < 0.05). Results: MTT viability data at 24 h showed that group VM and LU blocks were mildly cytotoxic, but there was no statistically significant difference when compared with other groups (p>0.05). It was determined that all blocks caused cell proliferation after 48 hours of exposure (p>0.05). It has been shown that all blocks whose cytotoxic effects were investigated did not cause any toxic effects (except VM and LU for 24 h) at different application times (24 h and 48 h). Conclusion: Based on the results obtained and the limitations of the current in vitro study, the tested materials were not cytotoxic. Only VM and LU caused negligible cytotoxicity at 24-hour exposure.